Dredging-induced turbid plumes affect bio-irrigation and biogeochemistry in sediments inhabited by Lanice conchilega (Pallas, 1766). (11th September 2018) - Mestdagh, Sebastiaan; Ysebaert, Tom; Moens, Tom; Van Colen, Carl
Abstract: Building man-made structures in coastal seas are often preceded by dredging operations, inducing turbid plumes of suspended sediment. To study the effects of such high-concentration sediment plumes on the suspension-feeding polychaete Lanice conchilega, a laboratory experiment was performed, in which individuals of L. conchilega were exposed to natural seawater with a suspended sediment concentration (SSC) of ∼ 0.3 g l −1 and treatments with elevated SSC of 5 and 1 g l −1, representing concentrations in a dredging plume at the moment of sediment release and after initial dilution, respectively. We measured clearance rates of sediment particles, biogeochemical fluxes, and bio-irrigation. While clearance rates and nitrite efflux significantly increased in both treatments with elevated SSC compared with the control, bio-irrigation increased at 1 g l −1 but was lowest at 5 g l −1 . It is suggested that piston pumping is intensified under intermediate concentrations to remove sediment, but ceases under high concentrations are due to sediment ingestion. By transporting oxygen into the sediment, bio-irrigation enhances aerobic microbial processes, among which nitrification. We conclude that short-term extreme suspended sediment concentrations can have a significant impact on the biogeochemistry of the seabed through changes in behaviour of L. conchilega .